1987
DOI: 10.4049/jimmunol.139.9.3107
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell inhibition of young spherules and endospores of Coccidioides immitis.

Abstract: The recent development of a method for culturing the parasitic form of Coccidioides immitis by using conditions compatible with the growth of lymphoid cells has enabled us to investigate the role of natural killer (NK) cells in defense against this pathogenic fungus. Pure cultures of spherules and endospores were grown in RPMI 1640 which contained 10% calf serum. Single cell suspensions of young spherules and endospores were incubated in the presence of freshly isolated human peripheral blood lymphocytes (PBL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Low numbers of NK cells are associated with increased prevalence of fungal infection, and there is a correlation between reduced NK cell cytotoxic activity and fungal infections [ 30 ]. NK cells have been shown to be active and cytotoxic against bacteria such as Salmonella typhimurium [ 31 ], Shigella flexneri [ 32 ], Mycobacterium tuberculosis [ 33 ], Staphylococcus aureus [ 34 ], Listeria monocytogenes [ 35 ], and Pseudomonas aeruginosa [ 36 ], and against mold and fungi such as Candida albicans [ 37 , 38 ], Cryptococcus neoformans [ 38 , 39 ], Aspergillus fumigatus [ 40 , 41 ], Paracoccidioides braziliensis [ 42 ], Coccidioides immitis [ 43 ], Bacillus anthracis [ 44 ], and Pneumocystis murina [ 45 ].…”
Section: Natural Killer (Nk) Cells and Their Subpopulationsmentioning
confidence: 99%
“…Low numbers of NK cells are associated with increased prevalence of fungal infection, and there is a correlation between reduced NK cell cytotoxic activity and fungal infections [ 30 ]. NK cells have been shown to be active and cytotoxic against bacteria such as Salmonella typhimurium [ 31 ], Shigella flexneri [ 32 ], Mycobacterium tuberculosis [ 33 ], Staphylococcus aureus [ 34 ], Listeria monocytogenes [ 35 ], and Pseudomonas aeruginosa [ 36 ], and against mold and fungi such as Candida albicans [ 37 , 38 ], Cryptococcus neoformans [ 38 , 39 ], Aspergillus fumigatus [ 40 , 41 ], Paracoccidioides braziliensis [ 42 ], Coccidioides immitis [ 43 ], Bacillus anthracis [ 44 ], and Pneumocystis murina [ 45 ].…”
Section: Natural Killer (Nk) Cells and Their Subpopulationsmentioning
confidence: 99%
“…While alveolar macrophages are present and neutrophils arrive rapidly upon spherule rupture, the role of innate lymphoid cells, NK cells, and eosinophils has not been characterized. Petkus and Baum [104] reported that NK cells are the leukocytes responsible for Coccidioides growth inhibition in vitro. This conclusion is hampered by their use of the Leu-11 antibody [104], which recognizes CD16 and is found not only on NK cells but also on neutrophils, monocytes, and macrophages.…”
Section: Unanswered Questionsmentioning
confidence: 99%
“…Petkus and Baum [104] reported that NK cells are the leukocytes responsible for Coccidioides growth inhibition in vitro. This conclusion is hampered by their use of the Leu-11 antibody [104], which recognizes CD16 and is found not only on NK cells but also on neutrophils, monocytes, and macrophages. The adaptive T-cell response is critical for establishment of long-term immunity, and optimizing this has been foundational for vaccine development efforts.…”
Section: Unanswered Questionsmentioning
confidence: 99%
“…In vitro , co-incubation setting against Coccidioides , human NK-enriched cells inhibited C. immitis endospores and spherules effectively. In this setting, interferon was used for immune augmentation and was shown to effectively enhance leucocyte-mediated fungal killing ( 101 ). As IL-2 appeared to enhance NK cell activation ( 102 ), this was added to CD16/CD56+ cell fractions against Cryptococcus with demonstrable efficacy ( 103 ).…”
Section: Development and Refinement Of Nk Cellular Anti-fungal Treatm...mentioning
confidence: 99%